Lisbon vs Porto: Contrasts in Urban Art Public Management - Castro, Ana Luísa; Gariso, Ana (Street Art & Urban Creativity, 2021)
Urban Art is considered one of the most important artistic movements of the 21st century and Portugal is not behind on this trend. Many of its cities are authentic open air museums and portuguese artists — like Vhils, Bordallo II and Mr. Dheo — are distinguished all over the World. The two main cities of Portugal — Lisbon and Porto — have invested a lot of their efforts, combating vandalism, legitimizing urban art, legalizing murals and supporting street artists. In Lisbon, GAU (Galeria de Arte Urbana) has sponsored dozens of legal murals and allowed for the painting of several others by private interests. Porto’s Urban Art Program started a few years later but has since funded several murals and authorized artistic events by private businesses. In this article two PHD students collaborate to analyze the development of urban art in both Lisbon and Porto, mainly focusing on the last decade; to understand the contrasts on the artistic management of public art; and to examine its possible impacts in Lisbon and Porto.